Intrinsic doping limitations in inorganic lead halide perovskites. Issue 2 (14th December 2021) - Sabino, Fernando P.; Zunger, Alex; Dalpian, Gustavo M.
Abstract : Design principles for an effective doping in halide perovskites: DP(i) – shallow transition levels; DP(ii) – pinning of Fermi level in conduction or valence band; DP(iii) – Large doping-induced Fermi level shift towards conduction or valence band. Abstract : Inorganic halide perovskites (HP's) of the CsPbX3 (X = I, Br, Cl) type have reached prominence in photovoltaic solar cell efficiencies, leading to the expectation that they are a new class of semiconductors relative to the traditional ones. Peculiarly, they have shown an asymmetry in their ability to be doped by holes vs. electrons. Indeed, both structural defect-induced doping as well as extrinsic impurity-induced doping strangely often result in HP's in a unipolar doping (dominantly p-type) with low free carriers' concentration. This raises the question whether such doping limitations presents just a temporary setback due to insufficient optimization of the doping process, or perhaps this represents an intrinsic, physically-mandated bottleneck. In this paper we study three fundamental Design Principles (DP's) for ideal doping, applying them via density functional doping theory to these HP's, thus identifying the violated DP that explains the doping limitations and asymmetry in these HP's. Here, the target DP are: (i) requires that the thermodynamic transition level between different charge states induced by the dopants must ideally be energetically shallow both for donors (n-type) or acceptors (p-type); DP-(ii) requires that the 'Fermi level pinning energies' for electrons E (n)pin and holes E (p)pin (being the limiting value of the Fermi level before a structural defect that compensate the doping forms spontaneously) should ideally be located inside the conduction band for n-type doping and inside the valence band for p-type doping. DP-(iii) requires that the doping-induced shift in equilibrium Fermi energy Δ E (n)F towards the conduction band for n-type doping (shift of Δ E (p)F towards the valence band, for p-type doping) to be sufficiently large. We find that, even though in HP's based on Br and Cl there are numerous shallow level dopants that satisfy DP-(i), in contrast DP-(ii) is satisfied only for holes and DP-(iii) fails for both holes and electrons, being the ultimate bottleneck for the n-type doping in Iodide HP's. This suggests an intrinsic mechanism for doping limitations in this class of semiconductors in terms of recognized physical mechanisms.